Salud mental en adultos víctimas del conflicto armado en situación de desplazamiento forzado en el municipio de Bajo Baudó (Chocó, Colombia). - Álvarez Moreno, Cerleny (Universidad Antonio Nariño, 2024)
Forced displacement according to the Constitutional Court represents around 10% of Colombians and has a great impact on the mental health of the victims. This research intends to determine, through the life stories that the population under study, the relationship between mental health and forced displacement, in victims in the context of the armed conflict between 23 and 60 years of age in the municipality of Bajo Baudó (Chocó) through the application of two objective tests: MINI neuropsychiatric interview and life stories. This investigation is of mixed focus, has a descriptive scope with a concurrent triangulation design. The results indicate that of the psychological disorders evaluated by the instruments, the most relevant in the displacement population are: Risk of suicide (57%), Major Depressive Episode (54%), Posttraumatic Stress Disorder (21%) and Disorder of generalized anxiety (43%); In addition, in the in-depth interview, permanent affectation was found on the psychological well-being scale. Due to this, it can be concluded that forced displacement has repercussions on mental health in the population victim of forced displacement in Bajo Baudo, Chocó.